Surgical management of hip instabilities in children with spina bifida [Spina bifidali çocuklarda kalça instabilitesinin tedavisi.] - (:unkn) unknown (My University, 2005)
OBJECTIVES: We evaluated the results of surgical management of hip instability in children with spina bifida (SB). METHODS: Twenty-eight hips of 26 patients (16 girls, 10 boys; mean age 4.5 years; range 3 to 6 years) were surgically managed for hip instability (subluxation/dislocation) associated with SB. Twenty-four patients (2 bilateral dislocations) had low-level lesions (L4-sacral) and a potential to walk, of which 16 patients presented with unilateral dislocation with functional problems including significant (>2 cm) limb-length discrepancy and scoliosis. Two patients had high-level lesions (thoracic-L3) associated with unilateral dislocations and were unable to walk. Those with a high-level lesion and some patients (9/26 hips) with a low-level lesion also had hip flexion contractures. Treatment included open reduction, pelvic osteotomy, proximal femoral osteotomy when necessary, and a spica cast. The patients were clinically and radiographically monitored for a mean of 38 months (range 30 to 48 months). RESULTS: Of 16 patients with functional problems, 14 patients had improvement in their gait patterns, while limb-length discrepancy and scoliosis persisted in two. The remaining 10 patients maintained their preoperative functional statuses. The mean range of motion of the hips decreased postoperatively; however, none of them developed joint stiffness. Early postoperative complications included superficial wound infections in three patients, and distal femoral diaphyseal fractures in two patients. Three patients required removal of the implants in the sixth month due to subcutaneous prominence thereof. Late radiographs of three patients showed recurrent subluxations, which did not require any intervention. CONCLUSION: Although surgical treatment of hip problems associated with high-level lesions may be unrewarding in children with SB, those associated with low-level lesions can be successfully managed with proper surgical indications.